(untitled) - Carpy, Sabrina; Berhanu, Michael; Chaigne, Martin; Courrech du Pont, Sylvain (Comptes Rendus. Physique, 2025)
Physical or chemical phase changes in ablation, such as sublimation, melting or dissolution, are studied in physics for their many engineering applications. At solid/fluid interfaces, the interaction between a phase change and a flow can lead to pattern formation. In this case, the fluid mechanics associated with such phase changes play a key role in the evolution of terrestrial and planetary landscapes, observed by probes orbiting planets and moons. On Earth, sea ice, glaciers and karst plateaus extend over meters or kilometers. The scale of these landscapes contrasts with the scale of the physical mechanisms that govern their evolutionary dynamics. Indeed, it is the typical size of atmospheric boundary layers or meltwater/vapor/solute films that constrain the heat/concentration transfer at the phase change/dissolution interface, and hence the rate of solid ablation. In many situations, these layers are controlled by fluid flow, either natural or forced convection. In the former case, the flow may be buoyancy driven by the melting/dissolution/sublimation itself, resulting in density stratification caused by, for example, temperature/concentration gradients. This stratification may be stable or unstable. In the second case, the flow forced by winds or slopes can be considered as a flow of an infinite height or of a finite height, such as shallow water flow. In all cases, the mass flux modifies topography, which in turn affects the boundary layer flows and thus the ablation rate in a retroactive way. In nature, the positive feedback between geometry and mass transfer drives the spontaneous formation of characteristic patterns at different scales. These patterns are not just geological curiosities, such as Zen stones or dirt cones but markers of the hydrodynamic processes at work. Many landscapes are shaped by regular, repeated patterns, whether sharp-edged, scalloped, parallel-crested, or stepped. By experimentally investigating different modes of flow transport on solid substrates undergoing physical or chemical phase change, this review aims to highlight the role of the flow transport mode in the diversity of patterns observed on analogous materials. Understanding the diversity of these patterns is key to assessing the environmental conditions under which they form on planets such as Mars or Pluto, where phase changes play a very important geomorphological role.